Social economic status, nutrition knowledge on food consumption behavior of poor family in Maros Regency, South Sulawesi – Indonesia - Nursiah, Andi; Idris, Idris; Briliannita, Anjar; Nurhaedah, Nurhaedah; Wijayanti, Lumastari Ajeng; Muslimin , Muslimin B (Institute of Computer Science (IOCS), 2024)
This study aims to find the effect of knowledge about nutrition on poor families in Maros Regency, South Sulawesi - Indonesia. To find the effect of socioeconomic status on food consumption behavior of poor families in Maros Regency. This type of research is ex-post facto using a quantitative approach with a survey method. The design or research model on the effect of exogenous variables, namely Socio-Economic Status is given a symbol (X1), Knowledge about nutrition is given a symbol (X2), and endogenous variables, namely Food Consumption Behavior are given a symbol (Y). The research locations are in Tukamasea Village, Mattoangin Village, Minasa Baji Village, and Alatengae Village, Bantimurung District, Maros Regency, South Sulawesi Province. More specifically, the main locus of research is poor families in 4 (four) villages in Bantimurung District, Maros Regency. The data obtained were analyzed using descriptive statistical analysis and inferential statistical analysis. The number of samples in this study was 200 households. The data analysis technique used is Path Analysis technique. The results of this study indicate that there are (1) there is an influence of socioeconomic status on consumption behavior, there is a direct and indirect effect of knowledge about nutrition on the food consumption behavior of poor families (direct influence), and knowledge about nutrition has an effect on lifestyle (indirect effect).